Analysis of Student Engagement in the Problem-Based Learning Model for Accounting Subject in the Merdeka Curriculum - Selviani, Ayudho; Devitriani, Helen (FKIP Universitas Halu Oleo, 2024)
This research is motivated by the awareness of students who need to be more active in the learning process to improve their understanding and skills. This study aims to determine the activeness of X.E class students through the Problem Based Learning model in economics subjects in implementing the independent curriculum at SMA Negeri 1 Kota Bengkulu. This research uses descriptive qualitative type. Data sources from economics teachers and students of class X.E. Data collection techniques with observation, interviews and documentation. Data analysis techniques are data reduction, data presentation and conclusion drawing. Data validity checking with triangulation, namely source triangulation. The results showed that student activeness through the Problem Based Learning model at SMA Negeri 1 Bengkulu City was quite good in doing the assignments given by the teacher, some students were very active and always wanted to express their opinions while others tended to be quiet or lacked confidence and, quite a lot of students actively asked questions at each meeting but there were still students who were shy or hesitant to ask directly, students also showed active participation in group discussions and students had various motivations in repeating exercise questions.